KEANEKARAGAMAN JENIS BAMBU (Bambusodae) DALAM KAWASAN HUTAN AIR TERJUN RIAM ODONG DUSUN ENGKOLAI KECAMATAN JANGKANG KABUPATEN SANGGAU - Isabella, Lidwina Listha; Usman, Fadillah H; Thamrin, Eddy (JURNAL HUTAN LESTARI, 2017)
The purpose of this study is to determine diversity of Bamboo (Bambusodae) and level of dominance. Determination of observation using purposive sampling method with plot size of 10 x 10 m. Based on identification result of research in the area of waterfall forest Riam Odong there are 3 types of Bamboo, among other Bamboo Poring (Dendrocalamus asper (Schultes f.) Backer ex heyne), Bamboo Munti (Schizostachyum sp), and Bamboo Buru (Schizostachyum zollingeri Stuedel). The most important index is Schizostachyum sp with value (INP=149,07%), followed by Schizostachyum zollingeri Stuedel with (INP=31,64%), lowest type is Dendrocalamus asper (Schultes f.) Backer ex heyne with value (INP=19,29%). The dominant species is Schizostachyum sp with highest dominance value (C=0,5555), while lowest is Dendrocalamus asper (Schultes f.) Backer ex heyne with value (C=0093). The highest diversity index Dendrocalamus asper (Schultes f.) Backer ex heyne nemely (H’= 0,9949) and type of Schizostachyum zollingeri Stuedel (H’=0,9817) while lowest diversity index for the types of Schizostachyum sp (H’=0,3779). The value of highest evennes of Bamboo was Dendrocalamus asper (Schultes f.) Backer ex heyne with an evennes of types of 0,3673 and lowest evennes found in Schizostachyum sp kind of 0,0743.Keywords: Bamboo, Diversity, Riam Odong Waterfall Forest